In Vitro and In Vivo Antitumor Activity of Cucurbitacin C, a Novel Natural Product From Cucumber - Wu, Dinglan; Wang, Zhu; Lin, Muqi; Shang, Yi; Wang, Fei; Zhou, JiaYi; Wang, Fei; Zhang, Xiantong; Luo, Xiaomin; Huang, Weiren (Frontiers in Pharmacology, 2019)
Cucurbitacin C (CuC), a novel analogue of triterpenoids cucurbitacins, confers a bitter taste in cucumber. Genes and signaling pathways responsive for biosynthesis of CuC have been identified in the recent years. In the present study, we explored the anti-cancer effects of CuC against human cancers in vitro and in vivo. CuC inhibited proliferation and clonogenic potential of multiple cancer cells in a dose dependent manner. Low dose CuC treatment induced cell cycle arrest at G1 or G2/M stage in different cancer lines, whereas high dose treatment of CuC caused apoptosis in cancer cells. PI3K-Akt signaling pathway was found to be one of the major pathways involved in CuC-induced cell growth arrest and apoptosis by RNA-Seq and western blotting. Mechanistic dissection further confirmed that CuC effectively inhibited the Akt signaling by inhibition of Akt phosphorylation at Ser473. In vivo CuC treatment (0.1 mg/kg body weight) effectively inhibited growth of cancer cells derived xenograft tumors in athymic nude mice and caused significant apoptosis. Our findings for the first time demonstrated the potential therapeutic significance of CuC against human cancers.